Antioxidant and Protective Effect of Ajuga chamaecistus ssp. tomentella on CCl4 -Induced Liver Toxicity in Rat - Maryam Heydari; Mahdi Vazirian; Seyede Nargess Sadati Lamardi; Niloofar Nazari; Omid Sabzevari (Traditional and Integrative Medicine, 2025)
Ajuga chamaecistus ssp. tomentella (known as “komafitoos”) has been used in traditional Persian medicine for treating various illnesses including liver ailments. This study aims to evaluate the antioxidant and hepatoprotective effect of A. chamaecistus ssp. tomentella.  Chloroform, ethyl acetate (EAF), and the remaining hydroalcoholic fractions were separated from the total extract of the aerial parts of the plant and their antioxidant activity was evaluated using radical scavenging assay method (2,2-diphenyl-1-picrylhydrazyl, DPPH). The EAF was assessed against carbon tetrachloride (CCl4)-induced toxicity in rats. Rats were parted into 7 groups each containing 6 animals: sham (normal saline), CCl4 (single dose of 1 mL/kg b.w., i.p.), treatment groups 3, 4, 5 (treated 7 days with 25, 50 or 100 mg/kg EAF, respectively, p.o.) and 6 (treated 7 days with 100 mg/kg silymarin, p.o.) following a single dose of 1 mL/kg CCl4, i.p.). Group 7 received 100 mg/kg ethyl acetate fraction for 7 days. Animals were sacrificed 24 h after the last dose and total protein content and biochemical parameters were assayed in the serum. Glutathione, malondialdehyde, and superoxide dismutase levels were measured in the liver homogenates. Histological changes in the liver tissue were examined using a light microscope. EAF showed the best antioxidant activity according to the DPPH free radical scavenging assay (IC50=60.5 µg/mL) in comparison to the other fractions. It significantly alleviated serum transaminase levels, alkaline phosphatase, alanine transaminase, aspartate aminotransferase, and lactate dehydrogenase, especially with 25 and 50 mg/kg doses. Treatment with EAF increased superoxide dismutase activity and glutathione content; while decreasing the malondialdehyde level similar to the Silymarin group. Histological examination further confirmed our biochemical findings. A. chamaecistus ssp. tomentella showed acceptable hepatoprotective activity, as described by traditional Persian medicine.